Research on the Development and School-Based Implementation of Regional Characteristic Study Tour Courses in Nehe ——A "Red Soul-Casting and Five-Themed Education" Practice for Senior High School Students - Jiabin Luo (Education Research on Study Tours and Practice, 2026)
Research-based learning practice is an important approach to implementing the fundamental task of fostering virtue and promoting the core competencies of senior high school students. Nehe City possesses rich regional resources, including the red culture of the Northeast Anti-Japanese United Army, cold-region ice and snow resources, black soil ecological environments, and local historical and cultural traditions, which provide a practical foundation for the development of regionally distinctive study tour curricula in county-level senior high schools. Taking Nehe No.1 Middle School as an example, this study explores the construction of a “Five-Themed Education” study tour curriculum system characterized by “Red Soul-Casting, Silver Will-Tempering, Green Wisdom-Enlightening, Ancient Culture-Nurturing, and Golden Empowerment, ”with a focus on cultivating patriotism, responsibility, and practical competence. The “Five-Themed Education” model is not a natural color classification, but a curriculum-themed symbolic system based on regional resources, encompassing red culture education, ice and snow practice education, ecological civilization education, local historical and cultural education, and rural social practice education. Based on the cognitive characteristics and developmental needs of senior high school students, the study develops a school-based curriculum system from the perspectives of curriculum objectives, curriculum content, learning tasks, implementation procedures, and curriculum evaluation, and constructs a progressive study tour curriculum implementation framework across different grade levels. The findings indicate that the curriculum system contributes to enhancing students’ historical identity, social responsibility, inquiry competence, and local cultural identity, while promoting the transformation of study tour practice from activity-based experience to curriculum-based and systematic education. Through the analysis of curriculum development, implementation mechanisms, and evaluation systems, this study summarizes the practical experience of school-based implementation of regionally distinctive study tour curricula in county-level senior high schools, with the aim of providing references for study tour curriculum construction in senior high schools.